DNA microarrays a molecular cloning manual - Bowtell David; Sambrook Joseph (New York Cold Spring Harbor Laboratory Press, 2002)
This book overall gives a good coverage of spotted microarray technology starting from the preparation of probes and slides to sample preparation and hybridization. In addition to expression profiling areas covered include uses of microarrays for analysis
Keywords: DNA microarrays; Laboratory manuals